2018
DOI: 10.1186/s12889-018-6107-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing within general practices in Europe: a mixed-methods systematic review

Abstract: BackgroundLate diagnosis of HIV infection remains a key challenge in Europe. It is acknowledged that general practitioners (GPs) may contribute greatly to early case finding, yet there is evidence that many diagnostic opportunities are being missed. To further promote HIV testing in primary care and to increase the utility of available research, the existing evidence has been synthesised in a systematic review adhering to the PRISMA guidelines.MethodsThe databases PubMed, Scopus and Embase were searched for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 63 publications
0
27
0
3
Order By: Relevance
“…Migration status may be one of the structural factors impeding access [60,61], but future research should explore this finding in more detail. HIV screening programs should consider this policy-practice gap, and invest more in further reducing thresholds to health care and HIV testing through tailored community-based initiatives [62] or in primarycare settings [63], in particular for women and those being undocumented.…”
Section: Discussionmentioning
confidence: 99%
“…Migration status may be one of the structural factors impeding access [60,61], but future research should explore this finding in more detail. HIV screening programs should consider this policy-practice gap, and invest more in further reducing thresholds to health care and HIV testing through tailored community-based initiatives [62] or in primarycare settings [63], in particular for women and those being undocumented.…”
Section: Discussionmentioning
confidence: 99%
“…However, the data also highlight that there is considerable room to increase the offer of testing in health care settings, particularly in primary care and emergency departments. Evidence from systematic reviews shows that, in primary care, barriers to testing are related to the clinician's knowledge [17,148], as well as the clinician's anxiety associated with raising the topic of HIV testing with patients [149]. Improving testing in primary care is important because in many countries more testing takes place in primary care than in specialized services, as those countries have a testing strategy that primarily uses GPs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of barriers to HIV testing in primary care settings in Europe identified a lack of familiarity with testing guidelines and issues of communication about sexual health. 12 Other studies have also raised the following concerns in primary care: lack of time to conduct HIV tests, mischaracterisation of pretest counselling as complex and time-consuming, concerns around result management and the belief that HIV test results were best delivered by staff with specialised training. 13,14 However, there is evidence that provision of specific training, practical tools or an HIV testing promotion programme may improve HIV testing rates in general practice, particularly in areas of high prevalence.…”
Section: Effectiveness Of the Pilot Processmentioning
confidence: 99%